Preparation method and application of single-layer MoS2-based polyester differentiated fiber

Through in-situ polymerization and melt spinning technology, the single-layer MoS2 nanosheets are combined with PET polymerization monomer, which solves the problem of insufficient dispersion of single-layer MoS2 nanosheets in polymers, and achieves high efficiency of single-layer MoS2-based polyester fibers Preparation, with excellent antibacterial and photothermal properties, suitable for large-scale production.

CN116479542BActive Publication Date: 2024-12-20ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310156814.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2024-12-20
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

At this stage, the preparation of single-layer MoS2-based polyester fiber has not been effectively realized. The uniform dispersion of single-layer MoS2 nanosheets in polymers is insufficient, which affects its performance and application.

Method used

By polymerizing the single-layer MoS2 nanosheets with PET polymerization monomer in situ, the hydroxyl group on the surface of the MoS2 nanosheets reacts with terephthalic acid, so that the PET molecules are linked to the surface of the nanosheets, and the single-layer MoS2 is prepared by melt spinning method Based on polyester differentiated fibers, improving compatibility and functionality between nanosheets and polyester.

Benefits of technology

It realizes the good dispersion and functional performance of single-layer MoS2 nanosheets in PET, improves spinning performance, antibacterial performance and photothermal performance, is suitable for large-scale preparation and is inefficient and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116479542B_ABST
    Figure CN116479542B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polyester differential fiber preparation, and discloses a single-layer MoS 2 The preparation method and application of polyester-based differentiated fibers include the following steps: (1) forming a single layer of MoS 2 Nanosheets were ultrasonically dispersed in ethylene glycol to prepare a dispersion; (2) MoS was prepared by in situ polymerization 2 / PET nanocomposite materials; (3) MoS 2 / PET nanocomposites were prepared by melt spinning to obtain single-layer MoS 2 The present invention allows PET molecular chains to be grafted onto a single layer of MoS 2 The surface of the nanosheets prevents the agglomeration of the nanosheets, greatly improving the compatibility between the nanosheets and polyester, while reducing stacking and improving its functionality, so that the polyester fiber has ultra-high antibacterial properties and photothermal conversion properties, and has no obvious effect on the conventional polymerization process, which is suitable for large-scale preparation at this stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of polyester differentiated fibers, and in particular to a preparation method of single-layer MoS2-based polyester differentiated fibers and applications thereof. Background Art

[0002] Polyester is a polyester fiber obtained by spinning polyethylene terephthalate (PET), and is currently the largest variety of synthetic fibers. Polyester fibers have high breaking strength and elastic modulus, excellent resilience, heat setting effect, heat resistance and light resistance, but with the rapid development of the times, the upgrading and innovation of polyester is an important goal of the current society.

[0003] Two-dimensional nanomaterials are sheet materials with high aspect ratios that can be blended with polymers as fillers and can produce significant material performance gains at extremely low concentrations. Common two-dimensional nanomaterials include graphene, carbon nitride, montmorillonite, molybdenum disulfide, etc. Monolayer molybdenum disulfide (MoS2) is an ideal two-dimensional nanomaterial with excellent mechanical, thermal stability, biocompatibility and optoelectronic properties. Due to the quantum confinement effect on the thickness of its atomic layer, it exhibits special structures and physical and chemical properties, especially the variable band gap and extremely fast electron transfer rate of the atomic layer, which makes it have very broad application prospects in the development of multifunctional nanocomposites.

[0004] Monolayer MoS2 has ultra-high near-infrared photothermal absorption and can convert solar energy into thermal energy. It is an ideal photothermal conversion material. It also has excellent antibacterial effects and can produce reactive oxygen species to damage bacteria and inhibit the growth of microorganisms. Therefore, monolayer MoS2 can be widely used in seawater desalination, wastewater purification, salt difference power generation, sterilization and disinfection. However, the specific surface area of ​​single-layer nanosheets is large, and it is easy to cause serious agglomeration and stacking in the matrix, which seriously affects the performance of two-dimensional materials. Therefore, good dispersibility of the material is the key to preparing nanocomposites with excellent performance.

[0005] Currently, MoS2 is mostly compounded with a polyester matrix in the form of physical blending or surface coating. For example, a Chinese invention patent with publication number CN110873473A discloses a photothermal conversion material, a preparation method thereof, and a solar photothermal conversion device. MoS2 can be attached to the fabric by soaking the fabric in a prepared reaction solution and then rinsing and drying. However, the process is complicated and MoS2 is easily deposited and stacked.

[0006] A Chinese invention patent with publication number CN104963028A discloses an antibacterial polyester fiber and a preparation method thereof, wherein a variety of reagents such as antibacterial agents, lubricants, and dispersants are added to PET for melt spinning. However, the stacked conventional nanoparticles cannot be separated under the mixing action of screw extrusion, thereby affecting the spinnability and continuity.

[0007] The Chinese invention patent with publication number CN113265763A discloses a near-infrared light-responsive electrospun PCL / MoS2 nanofiber membrane and its preparation method, which uses electrospinning technology and is suitable for clinical regeneration and repair of bone defects, but is not suitable for industrial production.

[0008] In summary, there is currently no technology to achieve the preparation of single-layer MoS2-based polyester fibers. The uniform dispersion of single-layer MoS2 nanosheets in the polymer will directly affect its performance and application. Summary of the invention

[0009] In order to solve the above-mentioned technical problems, the present invention provides a preparation method and application of a single-layer MoS2-based polyester differentiated fiber, in which a single-layer MoS2 nanosheet and a PET polymerization monomer are in situ polymerized, and the hydroxyl groups on the surface of the MoS2 nanosheet react with terephthalic acid to graft the PET molecular chains on the surface of the nanosheet, thereby obtaining differentiated fibers with good spinning performance, and at the same time having good antibacterial and photothermal properties.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a single-layer MoS2-based polyester differentiated fiber, comprising the following steps:

[0012] (1) ultrasonically dispersing a single-layer MoS2 nanosheet into ethylene glycol to prepare a dispersion;

[0013] (2) Preparation of MoS2 / PET nanocomposites by in situ polymerization;

[0014] (3) The MoS2 / PET nanocomposite material was melt-spinned to prepare single-layer MoS2-based polyester differentiated fibers.

[0015] The monolayer MoS2 is first uniformly dispersed in the ethylene glycol monomer in the form of a dispersion, and then the dispersion is added to the PET polymer monomer for in-situ polymerization. The hydroxyl groups on the surface of the MoS2 nanosheet react with terephthalic acid, so that the PET molecular chain is grafted on the surface of the nanosheet. Compared with conventional bulk nano-MoS2, the monolayer MoS2 nanosheet has more exposed hydroxyl groups, and both sides of the nanosheet can be grafted with polyester molecular chains, which greatly improves the compatibility between the nanosheet and polyester, and can prevent the agglomeration of MoS2 nanosheets in the polyester matrix. The effective grafting rate of the monolayer MoS2 nanosheet in the molecular chain is higher. Therefore, the monolayer MoS2 nanosheet can improve its functionality in PET while reducing stacking. In addition, the monolayer MoS2 nanosheet has a direct band gap structure, while the conventional bulk nano-MoS2 has no band gap structure. The covalent interaction between the monolayer MoS2 nanosheet and PET makes the composite material excellent in photothermal performance, and at the same time has good antibacterial and processing properties, and can obtain differentiated fibers with good spinning performance.

[0016] The introduction of a single layer of MoS2 in the present invention has no significant effect on the conventional polymerization process, and is therefore suitable for large-scale preparation at this stage, and does not require the addition of any coupling agent, dispersant, compatibilizer or other auxiliary agents. Therefore, the method of the present invention is lower in cost, more efficient and more suitable in the actual production process.

[0017] Preferably, in step (1), the average thickness of the single-layer MoS2 nanosheet is 0.5 to 1.5 nm, and the lateral size is 50 nm to 2 μm.

[0018] In order to improve the grafting rate and compatibility of single-layer MoS2 nanosheets in the PET molecular chain and enhance the interaction between single-layer MoS2 nanosheets and PET, it is necessary to further control the size parameters of the nanosheets so that their mutual synergy can be better and differentiated fibers with better spinning performance can be obtained.

[0019] Preferably, in step (1), the concentration of single-layer MoS2 nanosheets in the dispersion is 5 to 30 g / L; and the ultrasonic dispersion time is 0.5 to 2 h.

[0020] The concentration of nanosheets in the dispersion will affect its dispersibility, which in turn affects the dispersibility of the nanosheets in the polyester matrix.

[0021] Preferably, in step (2), the in-situ polymerization is: mixing terephthalic acid, a dispersion and a catalyst, sequentially carrying out an esterification reaction and a polycondensation reaction, and completing the reaction to obtain a MoS2 / PET nanocomposite material, wherein the single-layer MoS2 nanosheet accounts for 0.001 to 5% of the mass of the MoS2 / PET nanocomposite material.

[0022] Preferably, the molar ratio of terephthalic acid to ethylene glycol in the dispersion is 1:1.1-1.5.

[0023] Preferably, the esterification reaction is carried out by heating the mixture to 240-250° C. under nitrogen protection and reacting the mixture at a pressure of 100-500 kPa for 3-6 hours.

[0024] Preferably, the polycondensation reaction is: heating to 240-290° C. under nitrogen protection, and reacting for 2-4 hours at a pressure of less than 100 kPa.

[0025] Preferably, the catalyst is a titanium catalyst, an antimony catalyst or a germanium catalyst, the titanium catalyst is an oxide, an inorganic salt or an organic compound of titanium, the antimony catalyst is an oxide, an inorganic salt or an organic compound of antimony; the germanium catalyst is an oxide, an inorganic salt or an organic compound of germanium; the added amount of the catalyst is 0.01 to 0.05% of the mass of terephthalic acid.

[0026] Preferably, in step (3), the melt spinning is: the spinning temperature is 250-290° C., the winding speed is 500-5000 m / min; and the diameter of the single-layer MoS2-based polyester differentiated fiber is 5-50 μm.

[0027] In a second aspect, the present invention also provides an application of a single-layer MoS2-based polyester differentiated fiber obtained by the above preparation method in functional fabrics.

[0028] The functional fabric has antibacterial properties and has an antibacterial effect on Staphylococcus aureus, Candida albicans, and Escherichia coli. After washing 50 times, the antibacterial rate of each strain can still be maintained at above 98%; the functional fabric has heat generation properties and can be heated from room temperature to 30-60°C under the irradiation of a xenon lamp, the far-infrared radiation temperature rise is greater than 1.4, and the far-infrared emissivity is higher than 0.88.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The hydroxyl groups on the surface of the monolayer MoS2 nanosheets react with terephthalic acid, so that the PET molecular chains are grafted onto the surface of the nanosheets, preventing the aggregation of the monolayer MoS2 and greatly improving the compatibility between the nanosheets and polyester, while reducing the stacking and improving its functionality. The interaction between the monolayer MoS2 and PET makes the composite material have excellent photothermal properties.

[0031] (2) The introduction of a single layer of MoS2 has no significant effect on the conventional polymerization process, is suitable for large-scale preparation at the current stage, and does not require the addition of any coupling agent, dispersant, compatibilizer or other auxiliary agents. Therefore, the method of the present invention is lower in cost, higher in efficiency and more suitable in the actual production process;

[0032] (3) MoS2 / PET nanocomposites have ultra-high antibacterial properties and photothermal conversion properties, and have good processing properties, which can produce differentiated fibers with better spinning properties and functionality. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a picture of the single-layer MoS2-based polyester differential fiber prepared in Example 1 under a fluorescence confocal microscope;

[0034] Figure 2 TEM image of the internal dispersion of the single-layer MoS2-based polyester differentiated fiber prepared in Example 1;

[0035] Figure 3 This is a photothermal heating curve of the single-layer MoS2-based polyester differentiated fiber prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0037] Example 1

[0038] A method for preparing a single-layer MoS2-based polyester differential fiber comprises the following steps:

[0039] (1) Monolayer MoS2 nanosheets (the average thickness of the monolayer MoS2 nanosheets is 1.1 nm, and the lateral size is 50 nm to 2 μm) are ultrasonically dispersed in ethylene glycol for 1.5 h to obtain a dispersion, wherein the concentration of the monolayer MoS2 nanosheets is 15 g / L.

[0040] (2) Add terephthalic acid and dispersion into a reactor at a molar ratio of terephthalic acid to ethylene glycol of 1:1.3, add ethylene glycol antimony catalyst, wherein the amount of the catalyst is 0.05wt% of terephthalic acid, and stir evenly after sufficient mixing; heat to 240°C and pressure to 300 kPa under nitrogen protection, and carry out esterification reaction for 3.5 hours until no water is produced; then heat to 280°C and evacuate to carry out polycondensation reaction for 2.5 hours; terminate the reaction, and water-cooled pelletizing to obtain MoS2 / PET nanocomposite material, wherein the mass fraction of single-layer MoS2 nanosheets in the MoS2 / PET nanocomposite material is 0.5wt%.

[0041] (3) The MoS2 / PET nanocomposite material was spun, cooled, oiled, drawn and wound to obtain a single-layer MoS2-based polyester differentiated fiber. The spinning temperature was 265°C and the winding speed was 1000 m / min.

[0042] The average diameter of the single-layer MoS2-based polyester differentiated fiber prepared in Example 1 is 20 μm and is uniform yellow-brown in color.

[0043] Example 2

[0044] A method for preparing a single-layer MoS2-based polyester differential fiber comprises the following steps:

[0045] (1) Monolayer MoS2 nanosheets (the average thickness of the monolayer MoS2 nanosheets is 1.1 nm, and the lateral size is 50 nm to 2 μm) are ultrasonically dispersed in ethylene glycol for 1.5 h to obtain a dispersion, wherein the concentration of the monolayer MoS2 nanosheets is 9 g / L.

[0046] (2) Add terephthalic acid and dispersion into a reactor at a molar ratio of terephthalic acid to ethylene glycol of 1:1.3, add ethylene glycol antimony catalyst, wherein the amount of the catalyst is 0.05wt% of terephthalic acid, and stir evenly after sufficient mixing; heat to 240°C and pressure to 400 kPa under nitrogen protection, and carry out esterification reaction for 3 hours until no water is produced; then heat to 280°C and evacuate to carry out polycondensation reaction for 2.5 hours; terminate the reaction, and water-cooled pelletizing to obtain MoS2 / PET nanocomposite material, wherein the mass fraction of single-layer MoS2 nanosheets in the MoS2 / PET nanocomposite material is 0.3wt%.

[0047] (3) The MoS2 / PET nanocomposite material was spun, cooled, oiled, drawn and wound to obtain a single-layer MoS2-based polyester differentiated fiber. The spinning temperature was 265°C and the winding speed was 1000 m / min.

[0048] Example 3

[0049] A method for preparing a single-layer MoS2-based polyester differential fiber comprises the following steps:

[0050] (1) Monolayer MoS2 nanosheets (the average thickness of the monolayer MoS2 nanosheets is 1.1 nm, and the lateral size is 50 nm to 2 μm) are ultrasonically dispersed in ethylene glycol for 1.5 h to obtain a dispersion, wherein the concentration of the monolayer MoS2 nanosheets is 30 g / L.

[0051] (2) Add terephthalic acid and dispersion into a reactor at a molar ratio of terephthalic acid to ethylene glycol of 1:1.3, add ethylene glycol antimony catalyst, wherein the amount of the catalyst is 0.05wt% of terephthalic acid, and stir evenly after sufficient mixing; heat to 240°C and pressure to 350kPa under nitrogen protection, and carry out esterification reaction for 5h until no water is produced; then heat to 280°C and vacuumize to carry out polycondensation reaction for 2.5h; terminate the reaction, and water-cooled pelletizing to obtain MoS2 / PET nanocomposite material, wherein the mass fraction of single-layer MoS2 nanosheets in the MoS2 / PET nanocomposite material is 1.0wt%.

[0052] (3) The MoS2 / PET nanocomposite material was spun, cooled, oiled, drawn and wound to obtain a single-layer MoS2-based polyester differentiated fiber. The spinning temperature was 265°C and the winding speed was 1000 m / min.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that no single-layer MoS2 nanosheet is added.

[0055] (1) Add terephthalic acid and ethylene glycol in a molar ratio of 1:1.3 into a reactor, add ethylene glycol antimony catalyst, wherein the amount of the catalyst is 0.05wt% of terephthalic acid, mix well and stir evenly; heat to 240°C and pressure to 300 kPa under nitrogen protection, and carry out esterification reaction for 4 hours until no water is produced; then heat to 280°C and vacuumize to carry out polycondensation reaction for 2.5 hours; terminate the reaction, and water-cooled pelletizing to obtain PET slices.

[0056] (2) The PET chips are spun, cooled, oiled, drawn and wound to obtain polyester fibers. The spinning temperature is 265°C and the winding speed is 1000 m / min.

[0057] Comparative Example 2

[0058] The difference from Example 1 is that bulk MoS2 (MoS2 nanopowder, without single-layer nanosheet exfoliation) is added.

[0059] (1) Bulk MoS2 was ultrasonically dispersed in ethylene glycol for 1.5 h to obtain a dispersion, in which the concentration of bulk MoS2 was 15 g / L.

[0060] (2) Add terephthalic acid and dispersion into a reactor at a molar ratio of terephthalic acid to ethylene glycol of 1:1.3, add ethylene glycol antimony catalyst, wherein the amount of the catalyst is 0.05wt% of terephthalic acid, and stir evenly after sufficient mixing; heat to 240°C and pressure to 300 kPa under nitrogen protection, and carry out esterification reaction for 4 hours until no water is produced; then heat to 280°C and vacuumize to carry out polycondensation reaction for 2.5 hours; terminate the reaction, and water-cooled pelletizing to obtain MoS2 / PET nanocomposite material, wherein the mass fraction of multilayer MoS2 nanosheets in the MoS2 / PET nanocomposite material is 0.5wt%.

[0061] (3) When the MoS2 / PET nanocomposite material is spun, the spinning conditions cannot be met and serious accumulation occurs, resulting in blockage of the spinneret.

[0062] The polyester fibers in Examples 1-3 and Comparative Example 1 were woven using a small circular knitting machine with a needle gauge of 28, a needle cylinder diameter of eight inches, and a number of knitting machines of 8F to obtain polyester fabrics.

[0063] Antibacterial properties: The antibacterial effects of polyester fabrics on Staphylococcus aureus, Candida albicans and Escherichia coli were tested according to the methods in GB / T 20944-2008 "Evaluation of antibacterial properties of textiles" and FZ / T 73023-2006 "Antibacterial knitwear".

[0064] Photothermal conversion performance: The polyester fabric is exposed to sunlight, and the thermal imaging and real-time temperature are recorded by a thermal imager; the polyester fabric is exposed to a xenon lamp at room temperature, and the real-time temperature is recorded by a thermal imager to obtain the photothermal heating curve.

[0065] Table 1

[0066]

[0067] like Figure 1 The image shown is a single-layer MoS2-based polyester differential fiber in Example 1 under a fluorescence confocal microscope, indicating that the MoS2 nanosheets are evenly dispersed in the matrix, giving it a fluorescent effect. Figure 2 The figure shows the internal dispersion of MoS2 nanosheets in the polyester matrix in Example 1, further illustrating that the MoS2 nanosheets are evenly dispersed in the matrix.

[0068] As shown in Table 1, the bactericidal rate of the polyester fiber of the present invention against Staphylococcus aureus, Candida albicans and Escherichia coli is about 99%. After washing 50 times, the antibacterial rate of the above-mentioned bacteria can still be maintained above 98%, reaching the national textile industry AAA standard.

[0069] Example 1 is compared with Comparative Example 1. The fabric prepared in Example 1 is heated from 8°C to 62.0°C. The fabric prepared in Comparative Example 1 is heated from 8°C to 10.8°C. It can be seen that the single-layer MoS2-based polyester differential fiber prepared in the present invention has good photothermal conversion performance. Both are irradiated with a xenon lamp at room temperature, and the real-time temperature is recorded with a thermal imager to obtain a photothermal heating curve as shown in FIG. Figure 3 As shown, the heating rate of the single-layer MoS2-based polyester differential fiber prepared in Example 1 is much faster than that of the polyester fiber prepared in Comparative Example 1, which shows that the single-layer MoS2-based polyester differential fiber prepared in the present invention has good light-to-heat conversion performance. In addition, by comparing Example 1 with Comparative Example 2, the block MoS2 can only obtain a suspension when dispersed in ethylene glycol, and its dispersibility and compatibility in the polyester matrix are poor, and it is impossible to spin polyester fibers, while the single-layer MoS2 nanosheet can obtain a homogeneous colloidal solution when dispersed in ethylene glycol, so the dispersibility is better.

[0070] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a single-layer MoS2-based polyester differential fiber, characterized in that: The steps include: (1) Ultrasonic dispersion of single-layer MoS2 nanosheets in ethylene glycol to prepare a dispersion, wherein the average thickness of the single-layer MoS2 nanosheets is 0.5-1.5 nm, the lateral size is 50 nm-2 μm, and the concentration of the single-layer MoS2 nanosheets in the dispersion is 5-30 g / L; (2) mixing terephthalic acid, a dispersion and a catalyst, and sequentially performing an esterification reaction and a polycondensation reaction. After the reaction is completed, a MoS2 / PET nanocomposite material is obtained, wherein the single-layer MoS2 nanosheet accounts for 0.001-5% of the mass of the MoS2 / PET nanocomposite material; (3) The MoS2 / PET nanocomposite was melt-spinned to prepare single-layer MoS2-based polyester differentiated fibers.

2. The method for preparing a single-layer MoS2-based polyester differentiated fiber as claimed in claim 1, characterized in that: In step (1), the ultrasonic dispersion time is 0.5 to 2 hours.

3. The method for preparing a single-layer MoS2-based polyester differentiated fiber as claimed in claim 1, characterized in that: In step (2), the single-layer MoS2 nanosheet accounts for 0.3-1% of the mass of the MoS2 / PET nanocomposite material.

4. The method for preparing a single-layer MoS2-based polyester differentiated fiber as claimed in claim 1, characterized in that: The molar ratio of the terephthalic acid to the ethylene glycol in the dispersion is 1:1.1-1.

5.

5. The method for preparing a single-layer MoS2-based polyester differential fiber according to claim 1 or 4, characterized in that: The esterification reaction is as follows: heating to 240-250° C. under nitrogen protection, reacting for 3-6 hours under a pressure of 100-500 kPa.

6. The method for preparing a single-layer MoS2-based polyester differential fiber according to claim 1 or 4, characterized in that: The polycondensation reaction is as follows: heating to 240-290° C., reacting for 2-4 hours under a pressure of less than 100 kPa.

7. The method for preparing a single-layer MoS2-based polyester differential fiber as claimed in claim 1 or 4, characterized in that: The catalyst is a titanium catalyst, an antimony catalyst or a germanium catalyst; the added amount of the catalyst is 0.01-0.05% of the mass of terephthalic acid.

8. The method for preparing a single-layer MoS2-based polyester differential fiber according to claim 1, characterized in that: In step (3), the melt spinning is as follows: the spinning temperature is 250-290° C., and the winding speed is 500-5000 m / min.

9. Application of a single-layer MoS2-based polyester differentiated fiber prepared by the preparation method according to any one of claims 1 to 8 in functional fabrics.